HUBUNGAN KARAKTERISTIK INDIVIDU DENGAN KOMPETENSI WIRAUSAHA PETANI RUMPUT LAUT DI SULAWESI SELATAN - Syafiuddin Syafiuddin; Amri Jahi (Jurnal Penyuluhan, 2007)
Seaweed farmers are those farmers who have seaweeds farming in rural coastal area, as their moyor income. The objective of this study was to determine the degree of relationship between individual characteristics of seaweed farmers and their entrepreneurship or business competence. Data were collected in July to October2006 from the 280 seaweed farmers. Data were analyzed by Kendal Concordance and Tau_b Path analysis and Pearson procedures. The important results of the study were as follows: (1) most of them are young, low educated, family size is sedentary, low family income, low in media utilization and sedentary in experience, motivation and capital, (2) two groups of competence were perceived (competence-importance) showed that the existence of positive correlation or high agreement, (3) Degree of all individual characteristic showed high positive correlation or high agreement for rank ten component of entrepreneur or business competence, (4) Mostly individual characteristic have significant relationship to entrepreneurship competence with existence of indirect and direct influence to some individual characteristics through entrepreneur or business competence and also direct to productions and incomes of seaweed farmers